1969
DOI: 10.1017/s0033822200011413
|View full text |Cite
|
Sign up to set email alerts
|

Yale Natural Radiocarbon Measurements IX

Abstract: The present list represents a major portion of the samples measured since publication of the last date list in 1963. As in previous lists, dates are reported in terms of the 5568 yr half-life. Infinite dates are reported as beyond a limit equal to 2Q above background. Nearly all of the samples were measured in one of three quartz counters with backgrounds of 0.7 to 1.2 cpm per liter of effective counting volume at working pressures of about two atmospheres. The age errors quoted are based only on the standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
0
1

Year Published

1969
1969
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(50 citation statements)
references
References 91 publications
7
42
0
1
Order By: Relevance
“…We hope our results will clarify some points of the probabilistic interpretation of "infinite" dates and support the use of 2o-limit proposed by Stuiver (1969), and advocated recently by Stuiver and Polach (1977).…”
Section: Introductionsupporting
confidence: 80%
“…We hope our results will clarify some points of the probabilistic interpretation of "infinite" dates and support the use of 2o-limit proposed by Stuiver (1969), and advocated recently by Stuiver and Polach (1977).…”
Section: Introductionsupporting
confidence: 80%
“…The radiocarbon age obtained for the present study can be compared with those reported by Stuiver (1969), Watson & Wright (1969) and Griffiths et al (2001) obtained from samples in a core from Lake Mirabad, a small lake that fills a surface depression in the Asmari-rich debris of the rock avalanche near its distal limit (Fig. 7b).…”
Section: Landslide-dammed Lake Deposits and Datingsupporting
confidence: 66%
“…al., 1965Rubin and Alexander, 1958Sainsbury, 1967Sancetta and Robinson, 1983Spiker, et. al., 1978Stuiver, 1969 Stuiver, et v al., 1963Weber and Pewe, 1970Weber and Pewe, 1961 East-Central Ager, 1975 Ager, 1972 Blackwell, 1965 Brown and Kreig, 1983Brown, et. al., 1969Brown, et.…”
mentioning
confidence: 99%
“…al., 1970Parrish, 1980 Porter, 1967 Shacklette and Rubin, 1969 Spikep, et. al., 1978Stuckenrath and Mielke, 1973Stuiver, 1969 Tpautman and Will is, 1966 Southern Agep, 1976 Ager and Sims, 1981 Ager and Sims, 1981 Baptsch-Winklep, et. al., 1983Bowers, 1978a Carter and Galloway, in press Denton, 1974Denton and Karlen, 1977Dixon, 1983 Faiphall, et.…”
mentioning
confidence: 99%